2023
DOI: 10.3390/cancers15030642
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab versus Ramucirumab in EGFR-Mutated Metastatic Non-Small-Cell Lung Cancer Patients: A Real-World Observational Study

Abstract: The combination of bevacizumab or ramucirumab with epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) therapy, chemotherapy, or immunotherapy for non-small-cell lung cancer (NSCLC) patients with EGFR mutations could have survival benefits. However, no study, to date, has been conducted to compare the efficacy and safety of these two antiangiogenic therapies (AATs). Stage IIIB to IV EGFR-mutated NSCLC patients who received first-line EGFR-TKIs between January 2014 and May 2022 were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…15 p = 0.014). 32 In line with their findings, our study of patients receiving an anti-VEGF agent as an add-on treatment to the first-line EGFR TKI also demonstrated similar PFS (median PFS: 24.2 vs. 21.9 months) and OS (median OS: 33.5 months vs. not reached) in bevacizumab and ramucirumab users. We also found that worse PS and multiple (≥3) metastatic sites were independent prognostic factors for poorer PFS, while the type of anti-VEGF agent was not.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…15 p = 0.014). 32 In line with their findings, our study of patients receiving an anti-VEGF agent as an add-on treatment to the first-line EGFR TKI also demonstrated similar PFS (median PFS: 24.2 vs. 21.9 months) and OS (median OS: 33.5 months vs. not reached) in bevacizumab and ramucirumab users. We also found that worse PS and multiple (≥3) metastatic sites were independent prognostic factors for poorer PFS, while the type of anti-VEGF agent was not.…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of T790M mutation was not influenced by adding different anti‐VEGF agent. In a recent study evaluating the clinical outcomes of different anti‐VEGF agents as an add‐on therapy to an EGFR TKI, the rates of T790M detection were similar between patients using bevacizumab and ramucirumab (43.6% vs. 38.2%, p = 0.645) 32 . In line with the previous study, our study showed no significant difference in T790M detection rate between patients receiving add‐on bevacizumab and ramucirumab (32% vs. 63%) while only 64% of patients had T790M testing on disease progression.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sete deles agem mantendo o processo de ação antitumoral das células T, no qual pembrolizumabe, nivolumabe, cemiplimabe, atezolizumabe e durvalumabe (Figura 2a) agem se ligando ao sistema PD-1/PD-L1 e ipilimumabe e tremelimumabe se ligam ao CTLA-4 (Figura 2a) 41 . Ainda há dois mAb que agem inibindo a angiogênese, ramucirumabe e bevacizumabe (Figura 2c) 42 . Além disso, há o anticorpo biespecífico amivantamabe (Figura 2c) que bloqueia o processo de sinalização de divisão celular 43 .…”
Section: Anticorpos Monoclonais Para O Câncer No Brasilunclassified